Corporate computer forensics investigation adoption antecedents in Malaysia's critical information infrastructure agencies - Wan Abdullah, Wan Abdul Malek; Hussin, Nurussobah; Ahmad, Mohd Nazir; Samsudin, Ahmad Zam Hariro; Jalil, Abdurrahman (Faculty of Information Management, 2024)
To counteract computer-related crimes that have affected many companies, Computer Forensics, which involves obtaining and analyzing digital information for use as evidence in civil, criminal, or administrative cases, has become a focal point of attention for top management. The objective of this study is to assess Tornatzky's TOE innovation adoption model in relation to the Information Assurance of Corporate Computer Forensics Investigation’s Action Plan among 210 respondents from Malaysia’s Critical Information Infrastructure agencies. The research results demonstrate a strong relationship between the TOE model and the Information Assurance of Corporate Computer Forensics Investigation, specifically in anticipatory, process, and postincident measures, with the exception of Tornatzky’s organizational factor.